2015
DOI: 10.1161/jaha.115.002129
|View full text |Cite
|
Sign up to set email alerts
|

Risk Prediction in Aortic Valve Replacement: Incremental Value of the Preoperative Echocardiogram

Abstract: BackgroundRisk prediction is a critical step in patient selection for aortic valve replacement (AVR), yet existing risk scores incorporate very few echocardiographic parameters. We sought to evaluate the incremental predictive value of a complete echocardiogram to identify high‐risk surgical candidates before AVR.Methods and ResultsA cohort of patients with severe aortic stenosis undergoing surgical AVR with or without coronary bypass was assembled at 2 tertiary centers. Preoperative echocardiograms were revie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
11
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 37 publications
0
11
1
Order By: Relevance
“…These include myocardial extracellular matrix dysfunction, worsening myocardial fibrosis, decreased ventricular compliance, abnormal diastolic filling, and eventual CHF. Therefore, delaying AVI until symptoms develop is controversial …”
Section: Discussionmentioning
confidence: 99%
“…These include myocardial extracellular matrix dysfunction, worsening myocardial fibrosis, decreased ventricular compliance, abnormal diastolic filling, and eventual CHF. Therefore, delaying AVI until symptoms develop is controversial …”
Section: Discussionmentioning
confidence: 99%
“…structural data has been shown to provide incremental prognostic value in patients undergoing both coronary artery bypass grafting (CABG) and surgical aortic valve replacement (SAVR). [1][2][3] Studies have shown preoperative transthoracic echocardiographic parameters such as left ventricular systolic function, severity of mitral regurgitation, and tricuspid regurgitation to be associated with increased major adverse cardiac events or mortality after transcatheter aortic valve replacement (TAVR). [4][5][6] While much emphasis has been placed on systolic function of the left ventricle, until recently the relevance of preoperative left ventricular diastolic dysfunction (LVDD) on clinical outcomes after TAVR has received significantly less attention.…”
mentioning
confidence: 99%
“…7 Given the prevalence of LVDD in patients with aortic stenosis and its reported association with major adverse cardiac events after CABG and SAVR, an investigation of its impact on outcomes in the TAVR patient population is desperately needed. 2,8 We considered the possibility that patients with worse preoperative LVDD as assessed using (1) E/e' ratio, (2) left atrial volume index (LAVI), and (3) left ventricular mass index (LVMI) would have increased mortality after TAVR at 1 year postoperatively. After institutional approval, we reviewed our own single institutional TAVR experience at the time comprising 123 patients including all access routes.…”
mentioning
confidence: 99%
See 2 more Smart Citations